Implications of automated vehicles for accessibility and location choices: Evidence from an expert-based experiment. (April 2018) - Milakis, Dimitris; Kroesen, Maarten; van Wee, Bert
Abstract: In this paper, possible accessibility impacts of fully automated vehicles (AVs) are explored. A conceptual framework for those impacts is developed based on the model of four accessibility components (i.e. land use, transport, temporal and individual) of Geurs and van Wee (2004). Q-method is applied among a sample of seventeen international accessibility experts to explore heterogeneity among experts with respect to the impacts of AVs on accessibility, and study different views and clusters of experts. Q-method statements are deductively categorized according to four accessibility components of the conceptual framework. Three viewpoints were extracted, indicating that experts expect AVs to influence accessibility through all four accessibility components. Viewpoint A expects that accessibility benefits stemming from AVs will be highly uncertain, mainly because of induced travel demand that will likely cancel out travel time and cost savings of AVs in the long term. Viewpoint B anticipates that accessibility changes because of AVs will have two opposing implications for urban form: densification of city center and further urban sprawl. Finally, viewpoint C expects that those who can afford an AV will mainly enjoy AVs benefits, thus AVs will have more negative than positive implications for social equity. Highlights: Accessibility impacts of fully automated vehicles (AVs) are explored. Q-method is applied among a sample of seventeen international accessibility experts. AVs accessibility benefits are highly uncertain. AVs can induce densification of city center and further urban sprawl. AVs accessibility benefits will not be equally distributed among different social groups.